Modelo de administración y valoración de activos fijos para instituciones educativas aplicando las NIIFS como estrategias de control Caso : Colegio María de la Merced - Portoviejo. - Almeida Samaniego, Lupe Carolina (2011)
This paper focuses on the rules relating to Property Plant and Equipment where they present the way it recognizes an asset covering the Property, plant and equipment have to be qualified as an asset taking into account their essential, background and economic reality and not merely their legal form and the IASB says it is considered an asset when it is owned by an entity for use in the production or supply of goods and services, for rental to others or for administrative purposes, the use of which is for more than an accounting period and the entity that helps to monetize futures derivatives thereof and that the cost of the asset to the entity can be measured reliably.